Higher Purpose, Employees, and the Firm - Thakor, Anjan V (The Review of Corporate Finance Studies, 2025)
I present a theory of organizational higher purpose in which, in addition to profits, the firms’ owners and employees care about a purpose that guides decisions but transcends business goals. This purpose sacrifices profits but serves a greater good that generates positive utility for the owners and employees. Some purpose-driven firms insure employees against layoffs and may pay employees more or less than firms not offering such insurance. Whether purpose-driven firms offering layoff insurance pay employees more or less than purpose-driven firms not offering this insurance depends on the owner’s purpose-linked utility relative to the employee’s. (JEL D01, D21, D24, G03, G32)